Andrea Buer: capstone - Buer, Andrea, artist (Colorado State University. Libraries, 2020)
The artist's statement: An integral aspect of my growth as an artist has been an insatiable curiosity for how things function and how they can be combined to create something new. This goes hand in hand with my foundation in traditional sciences thanks to my intended goal of becoming a doctor, which has given me a unique perspective to explore. The diversity of my educational background shows up in my work. For example, my piece Presence used live tracking of a person in a space to effectively translate their movements into an audio and visual glitch that appeared on a prerecorded video. This utilized studies in anatomy and physiology alongside coding and film to create the effect. Presence was a critique on the impact that we have on our surroundings, sometimes unknowingly, a concern frequently addressed in my artwork this past year. Presence is but one of many pieces that require an interdisciplinary approach to realize the concept while addressing the issue that I am interested in. My art has always focused on the human experience alongside nature but has recently been refined to a more specific idea related to ancestry and local legends. Growing up, I was raised on stories and lore specific to not only my family heritage but to the mountains and rural plains we came from. This reconnection to my childhood resulted in an exploration of the spiritual realm. Specifically, I have begun to analyze both the modern and ancient phenomena of cryptids. Cryptids are creatures like Bigfoot or Hidebehind that have eyewitnesses, but little to no evidence to prove their existence. There are countless cryptids around the world, varying from one location to the next and they are often more prominent in rural areas that are inherently closer to nature. Humanity has this uncanny ability to create our own boogeymen out of the unknown and I want to analyze why this is and how it has changed over the centuries. Technology has advanced alongside reporting's of cryptids, and in some cases has given them an even stronger presence. I am interested in researching and creating art that digs into the phenomena of our created boogeymen and our relationship to them as our relationship with technology deepens in turn. My most recent works explore coding of interactive stories and games, using film to push the narrative of a world that intersects our own, bringing the cryptic and unsettling into a more personalized experience for the viewer/participant. This has been used in various projects of mine, from a coded website (Cryptids'R'Us) to surreal videos (Merging) and my biggest undertaking, a work in progress titled Cryptic Calling which will be a fully interactive game made in Unity. I hope to get people thinking about their own folklore and how, despite advances in technology and medical understanding, our modern minds continue to adapt and maintain these cryptic traditions in our lives.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art